Beyond discipline : from compliance to community - Kohn, Alfie (Association for Supervision and Curriculum Development, 2006)
In this 10th anniversary edition of an ASCD best seller, author Alfie Kohn reflects on his innovative ideas about replacing traditional discipline programs, in which things are done to students to control how they act, with a collaborative approach, in which we work with students to create caring communities. Features a new afterword by the author.